Maternal and neonatal outcomes in twin pregnancy: a prospective study - More, Nandkishore; Tondge, Ganesh; Dasila, Priyank Singh; Ujede, Ayyaj Mahemood (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Twin pregnancies are found to be associated with greater risks to the mother and the babies. The normal length of gestation for an average pregnancy is around 40 weeks however in multiple pregnancies (twins, triplets, quadruplets, etc) it is usually shorter. Methods: A prospective observational study of women with twin pregnancy was carried out in a tertiary care hospital, in Maharashtra, from October 2020 to October 2022 with the purpose to assess the maternal and neonatal outcomes. 100 women with twin pregnancies who were registered to the hospital were selected for the study as per the inclusion and exclusion criteria. Results: 64% of women with twin pregnancies were in the age group of 21-30 years. Most of them had pregnancy as a result of the spontaneous type of conception. It was found that the vaginally delivered twins (20%) were at gestational age above 37 weeks and 8% at less than 32 weeks. 38% of twins were delivered by LSCS (elective LSCS 6% and emergency LSCS 38%). The gestational age at the time of delivery was found as 35-37 weeks (Mean ±SD 36 ± 1.2). 46% of neonates were shifted to NICU. The incidence of low birth weight and respiratory distress was more in babies born at 37 weeks and below. It was also observed that the as gestational age increased the perinatal deaths decreased. Conclusions: Regular follow-up of women with twin pregnancies is necessary for attainment of positive outcomes.